1999
DOI: 10.1038/sj.bjc.6690479
|View full text |Cite
|
Sign up to set email alerts
|

The two phyto-oestrogens genistein and quercetin exert different effects on oestrogen receptor function

Abstract: We compared the oestrogenic and anti-oestrogenic properties of the two well-known phyto-oestrogens, genistein and quercetin, on the oestrogen-sensitive breast cancer cell line MCF-7. Genistein exerted a biphasic effect on growth of MCF-7 cells, stimulating at low and inhibiting at high concentrations, whereas quercetin was only growth inhibitory. At doses which did not inhibit cell growth, respectively 5 and 1 μ M , genistein and quercetin counteracted oestrogen- and transforming growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(75 citation statements)
references
References 26 publications
2
70
1
2
Order By: Relevance
“…Our results are comparable with the previous report that genistein had an inhibitory effect on steroid hormone synthesis in adrenal glomerulosa (Bodart et al 1995, Mesiano et al 1999, Aptel et al 1999, Ohno et al 2002, Leydig , and ovarian cells (Lacey et al 2005). Moreover, genistein, resveratrol, and quercetin have been shown to suppress the proliferation of several tumor cells (Miodini et al 1999, Mitchell et al 1999, Setchell & Cassidy 1999, Xing et al 2001. Since our assays were performed by the incubation with genistein for less than 30 h and 50 mM genistein had no obvious inhibitory effect on MA-10 cell proliferation during the first 48 h in the cultures (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are comparable with the previous report that genistein had an inhibitory effect on steroid hormone synthesis in adrenal glomerulosa (Bodart et al 1995, Mesiano et al 1999, Aptel et al 1999, Ohno et al 2002, Leydig , and ovarian cells (Lacey et al 2005). Moreover, genistein, resveratrol, and quercetin have been shown to suppress the proliferation of several tumor cells (Miodini et al 1999, Mitchell et al 1999, Setchell & Cassidy 1999, Xing et al 2001. Since our assays were performed by the incubation with genistein for less than 30 h and 50 mM genistein had no obvious inhibitory effect on MA-10 cell proliferation during the first 48 h in the cultures (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Phytoestrogens such as genistein, resveratrol, and quercetin are widely distributed in human and animal diet and have chemopreventive properties against estrogen-responsive diseases, including inhibition of tumor cell growth (Setchell & Cassidy 1999, Miodini et al 1999, Mitchell et al 1999, Xing et al 2001, lowering serum cholesterol, and prevention of bone loss in rodents (Mizutani et al 2000, Nakajima et al 2001, Wattel et al 2003. Genistein is the most potent estrogenic compound in soy and soy products.…”
Section: Introductionmentioning
confidence: 99%
“…Uterine weight increase, which is known to be a marker of estrogenicity, was also commonly observed when studied after exposure to estrogenic EDCs. Since genistein as well as RVT can act as mixed agonists/antagonists at the ERs (Miodini et al, 1999;Bowers et al, 2000), a prominent antagonistic pathway is suggested by the delay. Little is known about the mechanism of action of HPTE, the active isomer of lindane, Cooper et al (1989) suggesting an antiestrogenic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike other phytoestrogens, they can activate the growth-promoting effects of ERa, but the caveat exists that the IC 50s for the ERa is 100 times higher than the IC 50s for the ERb and thus difficult to reconcile with the evidence that activation of the ERb inhibits growth and might silence ERa activation through dimerization (see above). However, the inability of apigenin and quercetin to bind to ERa, except at very high doses, could explain why these flavones only exert growth-inhibitory effects (Miodini et al 1999, Yin et al 2001) although other cellular mechanisms may exist (see below). In this respect, it is interesting to note that resveratrol binds with comparable affinity to both receptor subtypes, though with 7000-fold lower affinity than oestradiol (Bowers et al 2000), and, whilst the growth-promoting activity of resveratrol at low doses appears to be dependent on ERa, growth-inhibitory effects may not be mediated by antagonizing this receptor (Basly et al 2000).…”
Section: Phytoestrogens and The Growth Of Breast Cancer Cells In Vitrmentioning
confidence: 99%